Prognostic Value of the Expression of p53 in Patients with Non-small Cell Lung Cancer - Simonida Jovanovska Crvenkovska; Ilievska Poposka, Biljana; Smichkoska, Snezhana; Zafirovska Ivanovska, Beti; Stefanovski, Tome; Metodieva, Marija; Petrushevska, Gordana (ID Design 2012/Scientific Foundation SPIROSKI, 2009)
Background. The p53 gene is frequently mutated in non-small-cell lung cancer (NSCLC). However, the effect of p53 gene mutations on patient prognosis remains unclear. Aim. The aim of this study is to determine the association of p53 abnormalities with clinical data and prognosis in patients with NSCLC. Material and Methods. Tumor tissues from 80 patients with NSCLC were assessed by immunohistochemistry for expression of p53. The immunohistochemical study was performed on formalin-fixed, paraffin-embedded sections using LCAB immunoperoxidase method with mouse anti-p53 monoclonal antibody (clone DO-7; DAKO). Results. Forty-three (53,75%) of 80 patients revealed aberrant immunostaining for p53. Except to the histological type of tumors, there was no correlation of p53 expression with the clinicopathologic features. The Kaplan-Meier survival analysis demonstrated that patients with p53 positive status had poor survival rate (p=0,005 by the Log Rank test= 7,914). In Cox, regression analysis p53 and performance status emerged as independent prognostic factors (p<0,009 and p<0,000 respectively). Conclusion. The results from this study indicated that the aberrant expression of p53 is significant and independent predictable prognostic factor for patients with NSCLC.